How do care staff in residential aged care facilities conceptualise their non-verbal interactions with residents with dementia and what relevance has this for how residents' preferences and capacity for decision-making are understood?. (July 2020) - Cameron, Nadine; Fetherstonhaugh, Deirdre; Bauer, Michael; Tarzia, Laura
This paper considers the significance of how staff in residential aged care facilities interpret the non-verbal communication and behaviour of residents vis-a-vis their assessments of residents' preferences and ability to participate in decision-making. It highlights the risks associated with staff members' failure to interpret residents' non-verbal communication and behaviour with reference to residents' backgrounds and prior experiences. It also considers how non-verbal communication implemented by staff may impact residents' emotional state and, as a consequence, decision-making abilities. Drawing on interview data with aged care staff from Queensland and Victoria, it demonstrates that care staff in residential facilities appear to rely heavily on non-verbal signals in assessing the decision-making capacity and preferences of residents with dementia. It also indicates that many staff fail to consider residents' non-verbal communication and behaviour with due consideration of residents' individual histories.